Spinocerebellar ataxias: from pathogenesis to recent therapeutic advances - Cui, Zi-Ting; Mao, Zong-Tao; Yang, Rong; Li, Jia-Jia; Jia, Shan-Shan; Zhao, Jian-Li; Zhong, Fang-Tian; Yu, Peng; Dong, Ming (Frontiers in Neuroscience, 2024)
Spinocerebellar ataxia is a phenotypically and genetically heterogeneous group of autosomal dominant-inherited degenerative disorders. The gene mutation spectrum includes dynamic expansions, point mutations, duplications, insertions, and deletions of varying lengths. Dynamic expansion is the most common form of mutation. Mutations often result in indistinguishable clinical phenotypes, thus requiring validation using multiple genetic testing techniques. Depending on the type of mutation, the pathogenesis may involve proteotoxicity, RNA toxicity, or protein loss-of-function. All of which may disrupt a range of cellular processes, such as impaired protein quality control pathways, ion channel dysfunction, mitochondrial dysfunction, transcriptional dysregulation, DNA damage, loss of nuclear integrity, and ultimately, impairment of neuronal function and integrity which causes diseases. Many disease-modifying therapies, such as gene editing technology, RNA interference, antisense oligonucleotides, stem cell technology, and pharmacological therapies are currently under clinical trials. However, the development of curative approaches for genetic diseases remains a global challenge, beset by technical, ethical, and other challenges. Therefore, the study of the pathogenesis of spinocerebellar ataxia is of great importance for the sustained development of disease-modifying molecular therapies.